Growth Strategy and Programs for the Business Of Mango Puree - Fruters - Stefano Nadika, Dominikus; Inggriantara, Alibasjah (The Indonesian Journal of Business Administration, 2016)
Abstract – Healthy lifestyle has become a growing trend in many developing countries and one of them is Indonesia. This lifestyle has been entered into terms of everyday life and one of them is a beverage. Therefore, there are many healthy food arise. One of them is Fruters, which has specialty in healthy products include mango puree. Fruters as a start-up business that will be in the uncertainties of business conditions and they will face the problems. Limited human resources as lack of people in the production if there are orders in very large quantities, the limited stock of products because minimum capacity of storage for raw material, adding sales network and distribution channels in order to increase sales significantly, the less effective marketing strategy is using social media to connect with the customer build relationship, and to increase brand awareness and provide them with engaging information. The purposed of this final project is to formulate the business strategy of Fruters to increase consumer confidence in its products, to develop the suitable strategy that can be implemented in Fruters to settle the business issue, and to design the implementation plan that can be applied. Some assessments have been done to understand the business condition that was experienced by Fruters. By using PEST analysis, Porter's five forces, and competitor analysis. It is known that Fruters has several threats and opportunities of the external business environment. Internal analysis are VRINE model and existing business model canvas.  Business strategies are summarized in the long-term plan for 5 (five) years. Keyword: Business Strategy, Healthy Food, Start-up Business